Hemodynamic assessment of indomethacin-induced fetal heart failure in high-output state - Tongsong T. (2014)
Hemodynamic study was performed on a 32-year-old woman presenting at 27 weeks' gestation. Ultrasound revealed a single normal fetus with mild cardiomegaly, polyhydramnios, and placental chorioangioma. Doppler study showed increased middle cerebral artery peak systolic velocity, normal Tei index, and forward flow of "a" wave with normal preload in the ductus venosus. Twelve hours after initiation of indomethacin for tocolysis, frank hydrops fetalis developed rapidly. The right ventricle showed poor contractility and performance. Markedly increased preload in ductus venosus with reversed "a" wave and pulsations in the umbilical vein were demonstrated. This study suggests that indomepacin treatment in fetal high-cardiac output state should be used with extreme caution. © 2013 Wiley Periodicals, Inc.